Impact of Foreign Direct Investment on the Vietnam's Economy - Do, Thi Ngoc Huyen; Štěrbová, Ludmila, 1957-; Smělá, Monika; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
The thesis focuses on how foreign direct investment affect the economy of Vietnam. The aim is to clarify the positive and negative impacts of FDI, thereby point out the causes of negative impacts and propose appropriate solutions to improve FDI inflow in the future. The thesis uses achievements in attracting FDI such as FDI inflow value, number and scale of projects to show the increasing importance of determining its effects on the economy, then using the collected data on exports, labor, technology, state budget, and environment to analyze whether the effects are good or bad. Finally, synthesizing the data to make future predictions and directions to ensure the greatest benefits from FDI. This thesis indicates that the disadvantages are as many as the advantages, and in order to improve the quality of FDI in the future, the most important thing is that Vietnam can recognize the negative impacts and specify the suitable direction, strategy.
Vedoucí práce: Ludmila Štěrbová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses